2005
DOI: 10.1111/j.1469-8137.2005.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Root proliferation and seed yield in response to spatial heterogeneity of below‐ground competition

Abstract: Here, we tested the predictions of a 'tragedy of the commons' model of below-ground plant competition in annual plants that experience spatial heterogeneity in their competitive environment. Under interplant competition, the model predicts that a plant should over-proliferate roots relative to what would maximize the collective yield of the plants. We predict that a plant will tailor its root proliferation to local patch conditions, restraining root production when alone and over-proliferating in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
171
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(184 citation statements)
references
References 27 publications
9
171
3
1
Order By: Relevance
“…We found that root systems of plants grown in small pots are smaller than those of plants grown in large containers. Several other studies (35)(36)(37)(38) have reported similar results. Gersani et al (37) and O'Brien et al (38) reported that the root system was larger when grown in two connected pots shared with the other plant than when grown alone in one pot.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We found that root systems of plants grown in small pots are smaller than those of plants grown in large containers. Several other studies (35)(36)(37)(38) have reported similar results. Gersani et al (37) and O'Brien et al (38) reported that the root system was larger when grown in two connected pots shared with the other plant than when grown alone in one pot.…”
Section: Discussionsupporting
confidence: 75%
“…Several other studies (35)(36)(37)(38) have reported similar results. Gersani et al (37) and O'Brien et al (38) reported that the root system was larger when grown in two connected pots shared with the other plant than when grown alone in one pot. Our results showing that the size of the root system increases when a small number of roots physically contact an obstacle, but overall root size decreases as greater numbers of root tips touch the object, suggest that root impedance may be one factor in this phenomenon.…”
Section: Discussionsupporting
confidence: 75%
“…[12][13][14]). Allocation to plant height in competition over light may be similarly costly (reviewed by Schmitt [15]), and in fact, artificial selection to minimize height in agricultural crops clearly demonstrates a collective benefit of reduced selfishness [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As the competition on the root region is perceived, the plant invests on roots, aiming at occupying the soil spaces more quickly and increasing the allocation of biomass to the root system (O'Brien et al, 2005). The high production of MSPR when the TEC 5718 cultivar competed only for soil resources may be associated to the perception of future competition and, consequently, it must promote a greater allocation of biomass to the root system when in the presence of competing corn plants.…”
Section: Resultsmentioning
confidence: 99%